I love cats - Matthias, Catherine; Dunnington, Tom (Chicago : Childrens Press, 1983)
Other animals may be very nice, but cats are the best ones to love.
"Prepared under the direction of Robert Hillerich.".
Includes word list.
1.7
2.
K-3
P-2.
Keywords: Animals -- Fiction; Cats -- Fiction; Animals -- Fiction; Cats -- Fiction; Readers (Elementary).